Eficacia de un programa cognitivo conductual para la disminución de los niveles de presión arterial. - Arrivillaga Quintero, Marcela (2022)
This paper presents the efficacy of a cognitive-behavioral intervention program to reduce blood pressure levels, through a quasiexperimental study with two groups -experimental and control-, pre and post intervention measures and intra-intergroup analysis design. The sample was composed of 94 hypertension patients controlled at a health care center from Cali, Colombia. Measures include pre and post intervention systolic and diastolic blood pressure levels, the Perceived S tress Scale and the Adherence to hypertension treatment questionnaire. The intervention decreased systolic blood pressure levels significantly , remained diastolic blood pressure levels controlled, decreased perceived stress level, and improved adherence to treatment significantly . The results of the study support the efficacy of cognitive behavioral interventions to control arterial hypertension.